Evaluation of the Antibacterial Material Production in the Fermentation of Bacillus amyloliquefaciens-9 from Whitespotted Bamboo Shark (Chiloscyllium plagiosum) - Wenjie Zhang; Ling Wei; Rong Xu; Guodong Lin; Huijie Xin; Zhengbing Lv; Hong Qian; Hengbo Shi (Marine Drugs, 2020)
Bacillus amyloliquefaciens-9 (GBacillus-9), which is isolated from the intestinal tract of the white-spotted bamboo shark (Chiloscyllium plagiosum), can secrete potential antibacterial materials, such as β-1,3-1,4-glucanase and some antimicrobial peptides. However, the low fermentation production has hindered the development of GBacillus-9 as biological additives. In this study, the Plackett−Burman design and response surface methodology were used to optimize the fermentation conditions in a shake flask to obtain a higher yield and antibacterial activity of GBacillus-9. On the basis of the data from medium screening, M9 medium was selected as the basic medium for fermentation. The data from the single-factor experiment showed that sucrose had the highest antibacterial activity among the 10 carbon sources. The Plackett−Burman design identified sucrose, NH4Cl, and MgSO4 as the major variables altering antibacterial activity. The optimal concentrations of these compounds to enhance antibacterial activity were assessed using the central composite design. Data showed that sucrose, NH4Cl, and MgSO4 had the highest antibacterial activities at concentrations of 64.8, 1.84, and 0.08 g L−1, respectively. The data also showed that the optimal fermentation conditions for the antibacterial material production of GBacillus-9 were as follows: Inoculum volume of 5%, initial pH of 7.0, temperature of 36 °C, rotating speed of 180 rpm, and fermentation time of 10 h. The optimal fermentation medium and conditions achieved to improve the yield of antibacterial materials for GBacillus-9 can enhance the process of developing biological additives derived from GBacillus-9.